Nanoflower spherical three-dimensional porous composite water electrolysis catalyst and preparation method and application thereof
Patent Information
- Application Number
- CN202311365002.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-10-20
AI Technical Summary
[0006]第二,高聚物粘合剂导致的低电导率使得在在负载粉末时还要加入一定量的导电添加剂,碳添加剂容易在高电位下被氧化和蚀刻,从而降低电极的电催化性能
(1)本发明基于过渡金属镍而非贵金属,通过现水热负载后煅烧的方法在原本本征活性较差的非贵金属的表面原位生长过渡金属的多元氧化物,利用他们的协同作用,充分降低催化剂的低过电位,在1 mol/L的KOH溶液中,10 mA/cm2的电流密度下,析氢只需要164 mV的过电位,并且具有较高的稳定性。由于本发明使用的是过渡族金属盐为原料,使得本发明具有普适性,对过渡金属的硫酸盐、硝酸盐、氯盐等均可适用。
Smart Images

Figure CN117626338B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of hydrogen production catalyst technology through water electrolysis, and in particular relates to a nano-flower-shaped three-dimensional porous composite water electrolysis catalyst, its preparation method, and its application. Background Technology
[0002] Compared to traditional fuels such as coal, oil, and natural gas, hydrogen energy boasts advantages such as zero carbon dioxide emissions, being green and pollution-free, renewable, and having a high calorific value, effectively responding to the ambitious goals of "carbon peaking" and "carbon neutrality." Currently, the main methods of hydrogen production are: fossil fuel reforming and water electrolysis. Fossil fuel reforming and industrial by-product hydrogen production account for approximately 97% of total hydrogen production, while water electrolysis accounts for about 3%. Fossil fuel hydrogen production and industrial by-product hydrogen production are the primary pathways for hydrogen production at present. However, these methods themselves lead to significant energy consumption and environmental pollution, contradicting the goals of green and clean energy. Therefore, water electrolysis is receiving increasing attention.
[0003] Currently, the common industrial water electrolysis voltage is 1.8 V - 2.0 V, higher than the theoretical voltage of 1.23 V for water decomposition. This is because an energy barrier exists during water dissociation, leading to overpotential. Overpotential causes the water decomposition process to consume more energy, increasing the production cost of green hydrogen. Currently, Pt / C and RuO2 (or IrO) are commonly used as electrocatalysts in water electrolysis. However, the use of precious metals such as Pt, Ru, and Ir results in high production costs, and the low abundance of precious metals and the poor stability of precious metal electrocatalysts further limit their practical application in achieving complete water decomposition. Therefore, developing a low-cost, highly active catalyst is urgently needed in modern society. Among numerous candidate materials, transition metal catalysts are considered the most promising alternatives to noble metals due to their high abundance, low cost, and noble metal-like electronic configuration, along with high conductivity and wide pH applicability. Common transition metal electrocatalysts include transition metal carbides, transition metal nitrides, transition metal (hydride) oxides, transition metal phosphides, and transition metal sulfides. Transition metal oxides (TMOs) are particularly popular alternatives to noble metal-based catalysts due to their low production cost and outstanding redox capabilities. Compared to their instability and easy solubility in acidic media, alkaline media provide higher stability for TMOs as catalysts.
[0004] However, due to the inherently low conductivity of transition metal oxides, the intrinsic conductivity of transition metals is relatively high. In order to further obtain high-performance catalytic effects, nanostructures are a widely adopted strategy. Due to their special specific surface area, nanostructures can significantly increase the catalytic sites of transition metal-based electrocatalysts.
[0005] Existing nanostructured catalysts have the following problems: First, when nanoparticles are loaded onto a matrix, additional polymer binders (such as polytetrafluoroethylene) are required. Due to the low conductivity of polymers, this increases the overall resistance of the catalyst, buries some catalytic active sites, and inhibits electron transport.
[0006] Secondly, the low conductivity caused by the polymer binder necessitates the addition of a certain amount of conductive additives when loading powder. Carbon additives are easily oxidized and etched at high potentials, thereby reducing the electrocatalytic performance of the electrode.
[0007] Third, due to the low adhesion between the catalyst powder and the substrate, the loading mass of nanocatalysts is usually less than 1 mg / cm-2. Under such loading conditions, the number of active sites will be greatly limited.
[0008] Fourth, during long-term or high-current electrocatalysis, the coated catalyst can easily peel off from the substrate. This makes the current preparation process of nano-electrocatalysts complex, cumbersome, costly, and short-lived. Summary of the Invention
[0009] The purpose of this invention is to overcome the defects of the prior art by providing a nano-flower-shaped three-dimensional porous composite water electrolysis catalyst, its preparation method, and its application.
[0010] The objective of this invention can be achieved through the following technical solutions: The first aspect of this invention provides a method for preparing a nano-flower-shaped three-dimensional porous composite water electrolysis catalyst, comprising the following steps: S1: Pickle the nickel foam and perform hydrophilic treatment, then clean and dry it for later use; S2: Mix and stir nickel salt, molybdenum salt, inhibitor, urea and water, then add the foamed nickel treated in S1 for a hydrothermal reaction, take out the reactants, wash and dry them, and then calcine them to obtain the initial product. S3: Mix and stir vanadium salt and urea, then add the initial product from S2 for a secondary hydrothermal reaction. Remove the reactants, wash and dry them, and then calcine them again to obtain a three-dimensional porous composite water electrolysis catalyst with nanoflower spherical structure.
[0011] Furthermore, in S1, the specific pickling operation is as follows: the nickel foam is immersed in 10% HCl and agitated under ultrasonic conditions for 10-30 minutes.
[0012] As a preferred embodiment of the present invention, in S1, the specific operation of pickling is as follows: the nickel foam is immersed in 10% HCl and shaken under ultrasonic conditions for 15 minutes.
[0013] Furthermore, in S1, the specific operation of the hydrophilic treatment is as follows: immerse the nickel foam in an acetone solution and shake and stir for 10-30 minutes.
[0014] In a preferred embodiment of the present invention, in S1, the specific operation of the hydrophilic treatment is as follows: the nickel foam is immersed in an acetone solution and shaken for 15 minutes.
[0015] Further, in S2, the nickel salt is one or more of nickel nitrate hexahydrate, nickel nitrate, nickel acetate, nickel chloride, nickel sulfate, nickel phthalocyanine, nickel acetylacetonate, and nickel perchlorate; In a preferred embodiment of the present invention, in S2, the nickel salt is nickel nitrate hexahydrate.
[0016] In S2, the molybdenum salt is one or more of sodium molybdate, ammonium molybdate, zinc molybdate, molybdenum chloride, molybdenum acetylacetonate, and molybdenum acetate. In a preferred embodiment of the present invention, in S2, the molybdenum salt is sodium molybdate.
[0017] In S2, the inhibitor is ammonium fluoride.
[0018] Furthermore, in S2, the ratio of the amount of nickel salt, molybdenum salt, inhibitor, urea, and water is (1-3) mmol: (1-3) mmol: (10-60) mmol: (5-30) mmol: (20-150) ml.
[0019] In a preferred embodiment of the present invention, in S2, the ratio of the amount of nickel salt, molybdenum salt, inhibitor, urea and water is 1 mmol:1 mmol:20 mmol:5 mmol:(20-50) ml.
[0020] Furthermore, in S2, the conditions for a single hydrothermal reaction are: a reaction temperature of 100℃-210℃ and a reaction time of 4-8 h; In a preferred embodiment of the present invention, in S2, the conditions for a single hydrothermal reaction are: a reaction temperature of 120°C and a reaction time of 6 hours. In S2, the conditions for a single calcination are: holding at 300-600℃ for 1-3 hours in an air atmosphere.
[0021] As a preferred embodiment of the present invention, in S2, the conditions for the first calcination are: holding at 450°C for 2 hours in an air atmosphere.
[0022] Further, in S3, the vanadium salt is one or more of sodium metavanadate, ammonium metavanadate, potassium metavanadate, sodium orthovanadate, vanadium oxysulfate, vanadium oxalate, vanadium tetrachloride, and vanadium oxychloride. In a preferred embodiment of the present invention, in S3, the vanadium salt is sodium metavanadate.
[0023] In S3, the molar ratio of the vanadium salt to urea is (1-3):(5-30). In a preferred embodiment of the present invention, in S3, the molar ratio of the vanadium salt to urea is 1:5.
[0024] In S3, the reaction operation of mixing and stirring vanadium salt and urea is as follows: stirring in a water bath at a temperature of 50-70℃ until the urea is completely dissolved.
[0025] As a preferred embodiment of the present invention, in S3, the reaction operation of mixing and stirring vanadium salt and urea is as follows: stirring in a water bath at a water bath temperature of 60°C until the urea is completely dissolved.
[0026] Furthermore, in S3, the conditions for the secondary hydrothermal reaction are: a reaction temperature of 150℃-210℃ and a reaction time of 4-8 h; In a preferred embodiment of the present invention, in S3, the conditions for the secondary hydrothermal reaction are: a reaction temperature of 180°C and a reaction time of 6 h. In S3, the conditions for secondary calcination are: holding at 300-600℃ for 1-3 hours in an air atmosphere.
[0027] As a preferred embodiment of the present invention, in S3, the conditions for secondary calcination are: holding at 450°C for 2 hours in an air atmosphere.
[0028] The second aspect of the present invention provides a nano-flower-shaped three-dimensional porous composite water electrolysis catalyst, which is prepared by the preparation method described in any one of claims 1-8.
[0029] The third aspect of the present invention provides an application of a nano-flower-shaped three-dimensional porous composite water electrolysis catalyst, which is used for hydrogen production by water electrolysis.
[0030] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention is based on transition metal nickel rather than noble metal. A multi-component oxide of the transition metal is grown in situ on the surface of the originally poorly active non-noble metal using a hydrothermal loading and calcination method. Utilizing their synergistic effect, the low overpotential of the catalyst is significantly reduced. In a 1 mol / L KOH solution, at 10 mA / cm², the overpotential is reduced to [value missing]. 2 At a given current density, hydrogen evolution requires only an overpotential of 164 mV and exhibits high stability. Because this invention uses transition metal salts as raw materials, it is universally applicable to sulfates, nitrates, chlorides, and other salts of transition metals.
[0031] (2) The three-dimensional skeleton support of the present invention uses nickel, a transition metal, which makes the present invention universal. It can be used for three-dimensional skeleton structures of other transition metals and other materials with conductive properties such as carbon cloth.
[0032] (3) This invention has the advantage of being able to be prepared on a large scale and rapidly. This invention employs the method of first growing a transition metal hydroxide on the surface of a three-dimensional metal framework, followed by high-temperature calcination to generate a multi-element metal oxide. Compared with the previously bonded and supported nanostructured electrocatalyst electrode, the self-supporting electrode with a catalytically active phase grown in situ on a conductive substrate has readily available raw materials, a simple preparation process, and rapid preparation, making it very suitable for large-scale promotion in industrial production to achieve industrialization.
[0033] (4) The present invention has strong controllability. In the present invention, different transition metal elements can be selected and the concentration of each element, the temperature and time of hydrothermal synthesis can be controlled to grow nano-multi-element oxides with different morphologies and particle sizes to achieve one’s own needs, thereby obtaining a catalyst that meets one’s own needs. Attached Figure Description
[0034] Figure 1 The images are scanning electron microscope (SEM) images of the NiMoO4 / NF water electrolysis catalyst, where a and b are the NiMoO4 / NF water electrolysis catalysts prepared in Example 1.
[0035] Figure 2 SEM images of NiMoO4-NiVO3 / NF composite catalysts prepared by hydrothermal treatment at 180 °C for 6 h with different NaVO3 additions are shown. In Example 2, a and d are NiMoO4-NiVO3 / NF composite catalysts prepared with 1.0 mmol of sodium metavanadate. In Example 5, b and e are NiMoO4-NiVO3 / NF composite catalysts prepared with 1.5 mmol of sodium metavanadate. In Example 6, c and f are NiMoO4-NiVO3 / NF composite catalysts prepared with 2.0 mmol of sodium metavanadate.
[0036] Figure 3 SEM images of NiMoO4-NiVO3 / NF composite catalysts prepared at different hydrothermal temperatures for 8 hours with a NaVO3 addition of 1.5 mmol are shown. In Example 7, a and d are the NiMoO4-NiVO3 / NF composite catalysts prepared at a hydrothermal temperature of 150 °C; b and e are the NiMoO4-NiVO3 / NF composite catalysts prepared at a hydrothermal temperature of 180 °C in Example 5; and c and f are the NiMoO4-NiVO3 / NF composite catalysts prepared at a hydrothermal temperature of 210 °C in Example 8.
[0037] Figure 4 The image shows the XRD pattern of the water electrolysis catalyst, where a is the surface peeled powder of the NiMoO4 / NF water electrolysis catalyst substrate after initial hydrothermal calcination in Example 1, and b is the surface peeled powder of the NiMoO4-NiVO3 / NF composite catalyst after hydrothermal treatment at 180 °C for 6 h with an addition of 2 mmol of sodium metavanadate in Example 2.
[0038] Figure 5 The HER curves of the catalysts prepared in Examples 2, 5 and 6 are shown.
[0039] Figure 6 The HER curves of the catalysts prepared in Examples 2, 9 and 10 are shown when potassium hydroxide is used as the electrolyte.
[0040] Figure 7 The HER curves of the catalysts prepared in Examples 2, 7 and 8 are shown when potassium hydroxide is used as the electrolyte.
[0041] Figure 8 The HER curves are for the catalysts prepared in Examples 1 and 2 when potassium hydroxide is used as the electrolyte. Detailed Implementation
[0042] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. These embodiments are based on the technical solution of the present invention and provide detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments.
[0043] Unless otherwise specified, all raw materials used in this invention are commercially available or can be prepared using conventional methods in the art.
[0044] Example 1 The purpose of this embodiment is to prepare NiMoO4 / NF electrocatalytic materials, and the specific preparation method is as follows: S1: Using multi-functional punching pliers, cut the Suzhou Yiminglong NI1026 type foamed nickel into 1 cm × 2 cm foamed nickel sheets with a 1 cm × 2 cm foamed nickel special blade. Place them in a 50 ml beaker, add 1M HCl, and ultrasonically wash for 15 min under stirring. Then, use acetone to ultrasonically clean for 15 min under stirring for hydrophilic treatment. Finally, use ethanol and deionized water to ultrasonically clean for 30 min. After cleaning, place in a dry and cool place to dry. S2: Dissolve 1 mmol (0.291 g) nickel nitrate hexahydrate, 5 mmol (0.3 g) urea and 20 mmol (0.74 g) ammonium fluoride in 70 ml of deionized water to prepare solution A. Separately, dissolve 1 mmol (0.242 g) sodium molybdate dihydrate in 10 ml of deionized water to prepare solution B. Slowly add solution B to solution A while it is being stirred using a disposable syringe. Mix solution A and solution B thoroughly to prepare solution C. Keep stirring for 15 minutes and then sonicate for 10 minutes to make the particles in solution C more evenly dispersed. Then use a pipette to measure 10 mL of anhydrous ethanol and add it to solution C. Continue stirring for 15 minutes. The metal salt solution and ligand solution were mixed evenly and transferred to a 100 mL stainless steel autoclave lined with Teflon. The treated NF foam nickel substrate was placed vertically and the temperature was slowly increased to 120°C at a heating rate of 2°C / min, and held at 120°C for 6 hours. The reaction vessel was allowed to cool naturally to room temperature. The foamed nickel sample was then picked up with tweezers and rinsed three times with alternating ethanol and deionized water to remove unreacted metal salts, ligands, and impurities. The cleaned foamed nickel was then transferred to an oven and dried at 70°C for 24 hours. The completely dried nickel foam was removed and placed flat inside a corundum ceramic boat. The corundum ceramic boat was then transferred to a muffle furnace and heat-treated at 450°C for 120 min (heating rate 2°C / min), followed by natural cooling to obtain NiMoO4 / NF.
[0045] Example 2 The purpose of this embodiment is to develop a nano-flower-shaped three-dimensional porous composite water electrolysis catalyst (NiMoO4-NiVO3 / NF), and the specific preparation steps are as follows: S1: Cut the purchased 110 PPI nickel foam into 1 cm × 2 cm nickel foam sheets using a multi-functional punch pliers with a 1 cm × 2 cm nickel foam-specific blade. Place the sheets in a 50 ml beaker, add 1 M HCl, and ultrasonically wash for 15 min under stirring. Then, ultrasonically clean with acetone under stirring for 15 min for hydrophilic treatment. Finally, ultrasonically clean with ethanol and deionized water for 30 min. After cleaning, place the sheets in a dry and cool place to dry. S2: Dissolve 1 mmol (0.291 g) nickel nitrate hexahydrate, 5 mmol (0.3 g) urea and 20 mmol (0.74 g) ammonium fluoride in 70 ml of deionized water to prepare solution A. Separately, dissolve 1 mmol (0.242 g) sodium molybdate dihydrate in 10 ml of deionized water to prepare solution B. Slowly add solution B to solution A while it is being stirred using a disposable syringe. Mix solution A and solution B thoroughly to prepare solution C. Keep stirring for 15 minutes and then sonicate for 10 minutes to make the particles in solution C more evenly dispersed. Then use a pipette to measure 10 mL of anhydrous ethanol and add it to solution C. Continue stirring for 15 minutes. The metal salt solution and ligand solution were mixed evenly and transferred to a 100 mL stainless steel autoclave lined with Teflon. The treated NF foam nickel substrate was placed vertically and the temperature was slowly increased to 120°C at a heating rate of 2°C / min, and held at 120°C for 6 hours. The reaction vessel was allowed to cool naturally to room temperature. The foamed nickel sample was then picked up with tweezers and rinsed three times with alternating ethanol and deionized water to remove unreacted metal salts, ligands, and impurities. The cleaned foamed nickel was then transferred to an oven and dried at 70°C for 24 hours. The completely dried nickel foam was removed and placed flat inside a corundum ceramic boat. The corundum ceramic boat was then transferred to a muffle furnace and heat-treated at 450°C for 120 min (heating rate 2°C / min), followed by natural cooling to obtain NiMoO4 / NF.
[0046] S3: Dissolve 1.0 mmol (0.291 g) sodium metavanadate in 35 ml of deionized water, transfer to a water bath, and stir at 60°C for 15 min until the sodium metavanadate is completely dissolved into a pale yellow transparent liquid; add 5.0 mmol (0.3 g) urea, stir for 3 min to fully dissolve the urea; The above solution was transferred to a 50 mL stainless steel autoclave lined with Teflon. The treated NiMoO4 / NF substrate was placed vertically into the autoclave and slowly heated to 180 °C at a heating rate of 2 °C / min. The autoclave was then held at 180 °C for 6 hours. The reaction vessel was allowed to cool naturally to room temperature. The foamed nickel sample was then picked up with tweezers and rinsed three times with alternating ethanol and deionized water to remove unreacted metal salts, ligands, and impurities. The cleaned foamed nickel was then transferred to an oven and dried at 70°C for 24 hours. The completely dried nickel foam was placed flat inside a corundum ceramic boat. The corundum ceramic boat was then transferred to a muffle furnace and heat-treated at 450 °C for 120 min (heating rate 2 °C / min), followed by natural cooling to obtain a nano-flower-shaped three-dimensional porous composite water electrolysis catalyst (NiMoO4-NiVO / NF).
[0047] Example 3 Compared with Example 2, most of the contents are the same, except that in S2, the ratio of nickel salt, molybdenum salt, inhibitor, urea and water is 1 mmol:1 mmol:10 mmol:5 mmol:20 ml, which yields a nano-flower-shaped three-dimensional porous composite water electrolysis catalyst (NiMoO4-NiVO / NF).
[0048] Example 4 Compared with Example 2, most of the contents are the same, except that in S2, the ratio of nickel salt, molybdenum salt, inhibitor, urea and water is 3 mmol:3 mmol:60 mmol:30 mmol:150 ml, which yields a nano-flower-shaped three-dimensional porous composite water electrolysis catalyst (NiMoO4-NiVO / NF).
[0049] Example 5 The process is largely the same as in Example 2, except that in S3, 1.5 mmol (0.4365 g) of sodium metavanadate was dissolved in 35 ml of deionized water to obtain the NiMoO4-NiVO3 / NF composite catalyst.
[0050] Example 6 The process is largely the same as in Example 2, except that in S3, 2.0 mmol (0.582 g) of sodium metavanadate was dissolved in 35 ml of deionized water to obtain the NiMoO4-NiVO3 / NF composite catalyst.
[0051] Example 7 The process is largely the same as in Example 2, except that in S3, the hydrothermal reaction temperature is set to 150 °C to obtain the NiMoO4-NiVO3 / NF composite catalyst.
[0052] Example 8 The process is largely the same as in Example 2, except that in S3, the hydrothermal reaction temperature is set to 210 °C to obtain the NiMoO4-NiVO3 / NF composite catalyst.
[0053] Example 9 The process is largely the same as in Example 2, except that in S3, the hydrothermal reaction time is set to 4 hours to obtain the NiMoO4-NiVO3 / NF composite catalyst.
[0054] Example 10 The process is largely the same as in Example 2, except that in S3, the hydrothermal reaction time is set to 8 hours to obtain the NiMoO4-NiVO3 / NF composite catalyst.
[0055] Characterization tests were performed on different embodiments: 1. SEM testing Test method: The surface of the prepared catalyst was tested using a Kussem ultra-high resolution desktop scanning electron microscope EM-30N at 25 ℃.
[0056] Test results are as follows Figures 1 to 3 As shown, where Figure 1 The images are scanning electron microscope (SEM) images of the NiMoO4 / NF water electrolysis catalyst, where a and b are the NiMoO4 / NF water electrolysis catalysts prepared in Example 1.
[0057] As shown in the figure, the prepared nickel molybdate nanospheres have a diameter of 2-5 micrometers and are uniformly distributed on the nickel foam, thus achieving the initial goal of reducing overpotential.
[0058] Figure 2 SEM images of NiMoO4-NiVO3 / NF composite catalysts prepared by hydrothermal treatment at 180 °C for 6 h with different NaVO3 additions are shown. a and d are the NiMoO4-NiVO3 / NF composite catalysts prepared in Example 2 with 1.0 mmol of sodium metavanadate; b and e are the NiMoO4-NiVO3 / NF composite catalysts prepared in Example 5 with 1.5 mmol of sodium metavanadate; and c and f are the NiMoO4-NiVO3 / NF composite catalysts prepared in Example 6 with 2.0 mmol of sodium metavanadate. As shown in the figures, the number of self-grown nickel vanadate (NiVO3) nanospheres on the NiMoO4-NiVO3 / NF composite electrocatalysts increases with increasing sodium metavanadate (NaVO3) addition. A large number of agglomerated nanosphere clusters are generated when the addition amount is 2 mmol.
[0059] Figure 3 SEM images of NiMoO4-NiVO3 / NF composite catalysts prepared at different hydrothermal temperatures and after 8 hours of hydrothermal treatment with a NaVO3 addition of 1.5 mmol are shown. Images a and d represent the NiMoO4-NiVO3 / NF composite catalyst prepared in Example 7 at a hydrothermal temperature of 150 °C; images b and e represent the NiMoO4-NiVO3 / NF composite catalyst prepared in Example 5 at a hydrothermal temperature of 180 °C; and images c and f represent the NiMoO4-NiVO3 / NF composite catalyst prepared in Example 8 at a hydrothermal temperature of 210 °C. The images clearly show that with a NaVO3 addition of 1.5 mmol and a reaction time of 8 h, the number of self-grown nickel vanadate (NiVO3) particles on the NiMoO4-NiVO3 / NF composite catalyst increases with increasing reaction temperature. However, when the temperature rises to 210 °C, the increased solubility of sodium molybdate and sodium vanadate results in only a thin layer of nickel vanadate nanospheres growing on the surface of the nickel foam, leading to a decrease in active sites.
[0060] 2. XRD test Test method: The powder stripped from the sample surface was analyzed using a Bruker D8 ADVANCE X-ray diffractometer with a Cu target at 25 ℃.
[0061] Test results are as follows Figure 4 As shown, a is the surface peeling powder of the NiMoO4 / NF water electrolysis catalyst substrate after initial hydrothermal calcination in Example 1, and b is the surface peeling powder of the NiMoO4-NiVO3 / NF composite catalyst after hydrothermal treatment at 180 °C for 6 hours with an addition of 2 mmol of sodium metavanadate in Example 2.
[0062] Analysis of the diffraction peaks reveals that nickel molybdate and nickel vanadate nanospheres were successfully generated on the surface of nickel foam through two hydrothermal processes and calcination, thus creating active sites.
[0063] 3. HER test Test Method: The samples were tested using a Shanghai Chenhua Instruments CHI600E electrochemical workstation at 25℃. KOH solution (1 mol / L) was used as the electrolyte. The prepared NiMoO4-NiVO3 / NF composite catalyst was mounted on a platinum electrode holder, and the calomel reference electrode and platinum electrode were assembled into the corresponding positions of the measuring cup and placed in the electrolyte. HER testing was performed on the prepared samples.
[0064] Test results are as follows Figures 5 to 8 As shown, where by Figure 5 The HER curves of the catalysts prepared in Examples 2, 5, and 6 using potassium hydroxide as the electrolyte show that, under the condition that other conditions remain unchanged, only the amount of sodium metavanadate (NaVO3) added is changed. The catalyst performance initially increases and then decreases with the increase of sodium metavanadate (NaVO3) addition. As the amount of sodium metavanadate (NaVO3) added increases, its overpotential gradually decreases. When the amount of sodium metavanadate (NaVO3) added is 1.5 mmol (Example 5), its overpotential reaches the lowest value. Further increasing the amount of sodium metavanadate (NaVO3) added to 2.0 mmol (Example 6) causes the overpotential to rise again. This phenomenon indicates that introducing nickel vanadate particles with a larger specific surface area can increase the active sites on the self-grown catalyst, thereby improving catalytic efficiency. Increasing the amount added can significantly reduce the low overpotential in the reaction process. However, when too much nickel vanadate crystal is introduced, it leads to the agglomeration of the catalyst active sites, which in turn reduces the electrocatalytic activity of the composite catalyst.
[0065] Figure 6The HER curves of the catalysts prepared in Examples 2, 9, and 10 using potassium hydroxide as the electrolyte are shown. From the figures, we can see that the HER catalytic performance of the NiMoO4-NiVO3 / NF composite catalyst electrocatalyst increases and then stabilizes with increasing hydrothermal synthesis holding time. Comparing the HER curves for 4 h (Example 9) and 6 h (Example 2), it can be seen that the electrocatalytic performance significantly increases with increasing holding time. When the holding time reaches 8 h (Example 10), the performance at 15 mA / cm² is significantly enhanced. 2 The overpotential at the time of holding time is almost the same as that at 6 hours (dashed line in the figure). This phenomenon indicates that NiVO3 particles require a certain amount of time to grow on NiMoO4 / NF. If the holding time is too short, the particle size is small, the number of active sites on the catalyst is relatively small, and its catalytic performance is also lower. When the holding time reaches 6 hours, the particle size growth of NiVO3 particles has basically reached its upper limit. Further increasing the holding time has little effect on the growth of NiVO3 particles, but instead increases energy consumption and reduces economic benefits.
[0066] Figure 7 The HER curves of the catalysts prepared in Examples 2, 7, and 8 using potassium hydroxide as the electrolyte are shown in the figure. As can be seen from the figure, under the condition that other experimental conditions remain unchanged, the HER performance of this catalyst initially increases and then rapidly decreases with changes in hydrothermal temperature. Starting from the nickel vanadate formation temperature, its electrocatalytic performance gradually improves with increasing holding temperature, but reaches its maximum value at 180 °C. Further increases in holding temperature result in a rapid decrease in electrocatalytic performance. This phenomenon indicates that with increasing holding temperature, the growth rate of nickel vanadate continuously increases, and the growth of nickel vanadate crystals is more complete, thus improving catalyst performance. However, when the holding temperature exceeds 180 °C, the growth of nickel vanadate is inhibited, and only a thin layer of nickel vanadate nanospheres is formed. This may be due to the excessively high temperature causing more nickel vanadate crystals to dissolve in the solution.
[0067] Figure 8 The HER curves of the catalysts prepared in Examples 1 and 2 are shown below, using potassium hydroxide as the electrolyte. The tests revealed that the HER overpotential of the NiMoO4-NiVO3 / NF composite electrocatalyst is only 164 mV (current density 10 mA / cm²). 2 Compared to the NiMoO4 / NF catalyst substrate, the underpass voltage decreased by 113 mV (current density of 10 mA / cm²). 2 ).
[0068] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.
Claims
1. A method for preparing a nano-flower-shaped three-dimensional porous composite electrolytic water catalyst, characterized in that, Includes the following steps: S1: Pickle the nickel foam and perform hydrophilic treatment, then clean and dry it for later use; the specific operation of hydrophilic treatment is to immerse the nickel foam in acetone solution and shake and stir for 10-30 minutes. S2: Mix and stir nickel salt, molybdenum salt, inhibitor, urea and water, then add the foamed nickel treated in S1 for a hydrothermal reaction, remove the reactants and wash and dry them, then calcine them once to obtain the initial product; the inhibitor is ammonium fluoride. The ratio of the amounts of nickel salt, molybdenum salt, inhibitor, urea, and water is (1-3) mmol: (1-3) mmol: (10-60) mmol: (5-30) mmol: (20-150) ml; The conditions for a single hydrothermal reaction are: reaction temperature of 100℃-210℃ and reaction time of 4-8 h; The conditions for the first calcination are: holding at 300-600℃ for 1-3 hours in air atmosphere; S3: mixing and stirring vanadium salt and urea, then adding the initial product from S2 for a second hydrothermal reaction, taking out the reactants and washing and drying them before a second calcination to obtain a three-dimensional porous composite water electrolysis catalyst with nano-flower spherical shape; the molar ratio of vanadium salt to urea is (1-3):(5-30); The conditions for the secondary hydrothermal reaction are: reaction temperature of 150℃-210℃ and reaction time of 4-8 h; The conditions for secondary calcination are: holding at 300-600℃ for 1-3 hours in air atmosphere.
2. The preparation method of the nano-flower-shaped three-dimensional porous composite electrolytic water catalyst according to claim 1, characterized in that, In S1, the specific pickling operation is as follows: immerse the nickel foam in 10% HCl and agitate it under ultrasonic conditions for 10-30 minutes.
3. The preparation method of the nano-flower-shaped three-dimensional porous composite electrolytic water catalyst according to claim 1, characterized in that, In S2, the nickel salt is one or more of nickel nitrate hexahydrate, nickel nitrate, nickel acetate, nickel chloride, nickel sulfate, nickel phthalocyanine, nickel acetylacetone, and nickel perchlorate. In S2, the molybdenum salt is one or more of sodium molybdate, ammonium molybdate, zinc molybdate, molybdenum chloride, molybdenum acetylacetonate, and molybdenum acetate. In S2, the inhibitor is ammonium fluoride.
4. The preparation method of the nano-flower-shaped three-dimensional porous composite electrolytic water catalyst according to claim 1, characterized in that, In S3, the vanadium salt is one or more of sodium metavanadate, ammonium metavanadate, potassium metavanadate, sodium orthovanadate, vanadium oxysulfate, vanadium oxalate, vanadium tetrachloride, and vanadium oxytrichloride. In S3, the molar ratio of the vanadium salt to urea is (1-3):(5-30). In S3, the reaction operation of mixing and stirring vanadium salt and urea is as follows: stirring in a water bath at a temperature of 50-70℃ until the urea is completely dissolved.
5. A nano-flower-shaped three-dimensional porous composite water electrolysis catalyst, characterized in that, The nano-flower-shaped three-dimensional porous composite water electrolysis catalyst was prepared using the preparation method described in any one of claims 1-4.
6. The application of the nano-flower-shaped three-dimensional porous composite water electrolysis catalyst as described in claim 5, characterized in that, This nano-flower-shaped, three-dimensional porous composite water electrolysis catalyst is used for hydrogen production via water electrolysis.
Citation Information
Patent Citations
Ruthenium-modified molybdenum-nickel nanorod composite catalyst as well as preparation method and application thereof
CN114875442A
Material for reducing and inlaying ultra-stable Ni nano-particles on nickel molybdate nano-rod and preparation method and application thereof
CN116497395A